Atypical actinobacillosis in bulls in Argentina : granulomatous dermatitis and lymphadenitis = Actinobacilose atípica em touros na Argentina: dermatite granulomatosa e linfadenite - Margineda, Carlos Augusto; Odriozola, Ernesto Raul; Moreira, Ana Rita; Canton, German Jose; Micheloud, Juan Francisco; Gardey, Pedro; Spetter, Lucas Maximiliano; Campero, Carlos Manuel (2017)
Actinobacillosis is a common cause of sporadic infection in cattle. It was mostly characterized as a pyogranulomatous inflammation of the tongue, but also soft tissues as lymph nodes, other digestive tract localization and skin. The aim of this study was to describe an episode of granulomatous dermatitis and lymphadenitis affecting a bull herd in Argentina during 2010. Actinobacillus lignieresii was isolated from samples collected from one of the affected bulls, and characteristic lesions were observed. Lesions other than 'wooden tongue' are usually uncommon; however, actinobacillosis should be included as a differential diagnosis for cutaneous diseases.